Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1086/511683
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Natural History of Osteonecrosis in HIV-Infected Adults

Abstract: HIV-infected patients are at approximately 100-fold greater risk of developing osteonecrosis than the general population. Disease progression is slower in asymptomatic patients than in symptomatic patients. Given the high frequency of total hip replacement in symptomatic patients, studies to assess preventive and treatment strategies are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 45 publications
2
94
0
6
Order By: Relevance
“…Highly active antiretroviral therapy for HIV-infected patients is associated with a higher incidence of ON [28]. Many studies [29][30][31] have shown an association of ON in HIVpositive individuals undergoing antiretroviral therapy.…”
Section: Othersmentioning
confidence: 99%
“…Highly active antiretroviral therapy for HIV-infected patients is associated with a higher incidence of ON [28]. Many studies [29][30][31] have shown an association of ON in HIVpositive individuals undergoing antiretroviral therapy.…”
Section: Othersmentioning
confidence: 99%
“…The Osteo-HIV service of the Institute of Orthope- Chart 2 -WOMAC score before the operation and after six and twelve months of follow-up, and presence of dyslipidemia and lipodystrophy. (3)(4)(5) . In the sample presented, we found that 83.3% were using protease inhibitors, 75% had dyslipidemia and 66.6% had lipodystrophic syndrome, and these findings were concordant with data in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Osteonecrosis of the femoral head has an estimated annual incidence of 4% in this population, and mean bilaterality of 57%. This is of concern because it affects a young group of patients, between their fourth and fifth decades of life, and presents evolution to collapse of the head and permanent partial incapacity in 80% of the cases that have had the disease for four years (3)(4)(5)(6)(7) .…”
Section: The Authors Declare That There Was No Conflict Of Interest Imentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are generally younger adults age 35 years to 45 years, and risk factors for 75%-90% of cases include chronic steroid use, alcoholism, smoking, hip trauma including femoral neck fractures and hip dislocations, and prior hip surgery. Other potential etiologies for osteonecrosis include childhood history of slipped capital femoral epiphysis (SCFE), deep sea diving or other hyperbaric conditions, systemic lupus erythematosus (SLE) and other connective tissue disorders, autoimmune diseases causing vasculitis, sickle cell anemia, coagulopathy such as thrombophilia or disseminated intravascular coagulation, human immunodeficiency virus (HIV) infection, hyperlipidemia, fat embolus syndrome, treatment of developmental hip dysplasia, chemotherapy and/or radiation, organ transplantation, chronic liver disease, Gaucher disease, gout, and metabolic bone disease [3,4,[6][7][8][9][10] . Males are affected up to three times more than females, and bilateral femoral head osteonecrosis is found in up to 75% of cases [3,5] .…”
Section: Epidemiologymentioning
confidence: 99%